Use of Radical Cystectomy for Patients With Invasive Bladder Cancer - Gore, John L.; Litwin, Mark S.; Lai, Julie; Yano, Elizabeth M.; Madison, Rodger; Setodji, Claude; Adams, John L.; Saigal, Christopher S. (JNCI : Journal of the National Cancer Institute, 2010)
Background Evidence-based guidelines recommend radical cystectomy for patients with muscle-invasive bladder cancer. However, many patients receive alternate therapies, such as chemotherapy or radiation. We examined factors that are associated with the use of radical cystectomy for invasive bladder cancer and compared the survival outcomes of patients with invasive bladder cancer by the treatment they received. Methods From linked Surveillance, Epidemiology, and End Results–Medicare data, we identified a cohort of 3262 Medicare beneficiaries aged 66 years or older at diagnosis with stage II muscle-invasive bladder cancer from January 1, 1992, through December 31, 2002. We examined the use of radical cystectomy with multilevel multivariable models and survival after diagnosis with the use of instrumental variable analyses. All statistical tests were two-sided. Results A total of 21% of the study subjects underwent radical cystectomy. Older age at diagnosis and higher comorbidity were associated with decreased odds of receiving cystectomy (for those ≥80 vs 66–69 years old, odds ratio [OR] = 0.10, 95% confidence interval [CI] = 0.07 to 0.14; for Charlson comorbidity index of 3 vs 0–1, OR = 0.25, 95% CI = 0.14 to 0.45). Long travel distance to an available surgeon was associated with decreased odds of receiving cystectomy (for >50 vs 0–4 miles travel distance to an available surgeon, OR = 0.60, 95% CI = 0.37 to 0.98). Overall survival was better for those who underwent cystectomy compared with those who underwent alternative treatments (for chemotherapy and/or radiation vs cystectomy, hazard ratio of death = 1.5, 95% CI = 1.3 to 1.8; for surveillance vs cystectomy, hazard ratio of death = 1.9, 95% CI = 1.6 to 2.3; 5-year adjusted survival: 42.2% [95% CI = 39.1% to 45.4%] for cystectomy; 20.7% [95% CI = 18.7% to 22.8%] for chemotherapy and/or radiation; 14.5% [95% CI = 13.0% to 16.2%] for surveillance). Conclusions Guideline-recommended care with radical cystectomy is underused for patients with muscle-invasive bladder cancer. Many bladder cancer patients whose survival outcomes might benefit with surgery are receiving alternative less salubrious treatments.